Corporate social investment practitioners' experiences of corporate-NPO partnerships : a case study in the financial sector - Nyandeni, Refilwe (My University, 2015)
The government of South is faced with the triple challenges of poverty, unemployment and inequality. Addressing the various socio-economic challenges is a collective responsibility between the government, the private sector as well as non-profit organizations (NPO). NPOs are known to have a better understanding of the community challenges and can effectively target poverty in their constituencies. The United Nations (UN) in its Millennium Development Goals locates partnerships as an effective development strategy. In South Africa, corporate-NPO partnerships have contributed immensely in addressing a milieu of community challenges and building capacities of the grassroots citizens in line with the White Paper for Social Welfare. However there have been challenges between corporates and NPOs and this strains the relationship. Hence the aim of the research was to explore the challenges and the successes experienced by the corporate social investment practitioners at financial institutions in Johannesburg in their CSI partnerships with NPOs. The research adopted a qualitative case study design in the financial sector and interviewed 13 participants. Semi-structured interviews were conducted and data were analyzed using the thematic content analysis. The study found out that most corporate-NPO partnerships are monetary based and NPOs have the primary responsibility to facilitate community-based interventions. It is hoped that the recommendations will assist to encourage greater participation of corporate institutions in community programmes. This information will further contribute in occupational social work knowledge regarding participatory approaches in corporate-NPO partnerships.
A research presented to The Department of Social Work School of Human and Community Development Faculty of Humanities University of the Witwatersrand In partial fulfilment of the requirements For the degree Masters in Occupational Social work March 2015